Bio-psycho-social health assessment in prehospital emergency technicians: A systematic review - Vahid Delshad; Marcus Stueck; Abbas Ebadi; Mariola Bidzan; Hamidreza Khankeh (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Health is a complex structure and has physical, psychological, and social approaches. The importance and impact of health assessment have caused considerable attention to be paid to the employees of the health system and the determining factors of this relationship. Hence, the main purpose of this study was to find out the bio-psycho-social health situation in prehospital emergency technicians as the research question staff. MATERIALS AND METHODS: The present study is a systematic review and data have retrieved through extensive search in Scopus, Web of Science, PubMed (including Medline), Cochrane Library, Irandoc, Magiran, MedLib, and SID databases with a combination of keywords of "Health, " "Assessment, " "Social," "Psychological," "Biological," "Emergency," and "prehospital," according to the search strategy, between 2000 and 202111 studies were reviewed; then, they were entered based on the objectives of the study and narrative analysis was performed by the researcher. RESULTS: After analyzing the articles, a total of 4 factors affecting bio-psycho-social health in prehospital emergency technicians have been extracted and identified, which included health management, bio-psycho-social factors, occupational factors, and behavioral factors. CONCLUSION: This research showed four factors, namely health management, bio-psycho-social factors, occupational factors, and behavioral factors which could be effective in Bio-Psycho-Social health. Since prehospital emergency services have an important role in maintaining the health of the community, which requires attention to the bio-psycho-social health of emergency personnel, more studies have focused on health management among the four mentioned factors, but the need to examine the other three factors for a more accurate assessment of the health of emergency personnel seems necessary. Therefore, prevention and response strategies based on bio-psycho-social health assessment models are proposed to promote the health of prehospital emergency technician staff.